2018
DOI: 10.1016/j.apmr.2018.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Behavior-Change Intervention Targeting Physical Function, Walking, and Disability After Dysvascular Amputation: A Randomized Controlled Pilot Trial

Abstract: The behavior-change intervention demonstrates promise for increasing walking activity for people with dysvascular transtibial amputation (TTA). The efficacy of implementing such intervention in the scope of conventional TTA rehabilitation should be further studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
100
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(108 citation statements)
references
References 51 publications
(42 reference statements)
2
100
1
5
Order By: Relevance
“…66,67 For example, conventional rehabilitation interventions may improve physical function, but unless low self-efficacy and/or motivation are addressed with rehabilitation, increased physical activity following dysvascular LLA may not be achieved. 7,[68][69][70][71][72][73][74] Our results support the use of interventions targeting improved chronic disease self-management to improve daily step counts for people with dysvascular LLA. Chronic disease self-management interventions largely seek to enhance self-efficacy and motivation for positive health behaviors (eg, physical activity, medication adherence) by developing psychosocial skills known to positively influence health outcomes.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…66,67 For example, conventional rehabilitation interventions may improve physical function, but unless low self-efficacy and/or motivation are addressed with rehabilitation, increased physical activity following dysvascular LLA may not be achieved. 7,[68][69][70][71][72][73][74] Our results support the use of interventions targeting improved chronic disease self-management to improve daily step counts for people with dysvascular LLA. Chronic disease self-management interventions largely seek to enhance self-efficacy and motivation for positive health behaviors (eg, physical activity, medication adherence) by developing psychosocial skills known to positively influence health outcomes.…”
Section: Discussionsupporting
confidence: 60%
“…Although cardiovascular disease and low pre‐amputation walking time are not modifiable following dysvascular LLA, personal factors associated with these variables (eg, self‐efficacy, motivation) may be particularly important for interventions to improve physical activity . For example, conventional rehabilitation interventions may improve physical function, but unless low self‐efficacy and/or motivation are addressed with rehabilitation, increased physical activity following dysvascular LLA may not be achieved …”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Home-based behavior change intervention to promote exercise, walking activity, and disease self-management has been piloted in people recovering from nontraumatic transtibial amputation, resulting in increased daily step count. 19 However, the intervention did not focus solely on physical activity. In addition, the previous trial was implemented within the first 6 months after amputation and physical activity progression was potentially limited due to the need for some participants to resolve wound and incision healing issues from the amputation.…”
Section: Introductionmentioning
confidence: 99%
“…Only one intervention study was identified from the set of upper-limb studies and this used a log of grasping events to explore the effect of sensory feedback on use over time. 71 The lifestyle interventions for lower-limb prosthesis users were aimed at promoting physical activity, 67,69,81 providing rehabilitation 86 or providing massage. 80 These all showed positive outcomes, from increased daily step counts 67 to weight loss 81 and decreased pain levels.…”
Section: Figure 1 Flow Chart Of Selection and Sorting Methodsmentioning
confidence: 99%
“…71 The lifestyle interventions for lower-limb prosthesis users were aimed at promoting physical activity, 67,69,81 providing rehabilitation 86 or providing massage. 80 These all showed positive outcomes, from increased daily step counts 67 to weight loss 81 and decreased pain levels. 101 Of the 17 papers that compared activity levels of lower-limb prosthesis users to clinical scores, most compared the recorded physical activity to the K-level scores and found good correlation.…”
Section: Figure 1 Flow Chart Of Selection and Sorting Methodsmentioning
confidence: 99%